THE USE OF MIND MAPPING TECHNIQUE TO DEVELOP THE STUDENTS SPEAKING ABILITY - Ode Wani; Nurdevi Bte Abdul; Eka Prabawati , (Jurnal Keguruan dan Ilmu Pendidikan (JKIP), 2019)
This classroom action research aimed at finding out whether or not the use of Mind Mapping Technique effective to improve students’ speaking accuracy at the eleventh grade students’ of SMA Muhammadiyah Unismuh Makassar. The subject of the research was on second years IPA 1 students of SMA Muhammadiyah Unismuh Makassar in the academic year 2018/2019. The subject consisted of 24 students.Based on the findings, the result of the research shown that the use of mind mapping technique improved the students’ speaking skill in term of accuracy of vocabulary in speaking . It was proved by the mean score accuracy of vocabulary was (8.2%) from the mean score of the test in the cycle I is 66.4 to be 74.6 in the test in the end of cycle II. It indicates that the score of the students’ speaking skill in term of accuracy in vocabulary in each indicators in cycle II were greater than cycle II after implemented Mind Mapping as a technique in teaching speaking. As a conclusion, the implementation of Mind Mapping technique in teaching speaking is very effective. This technique has a positive influence in improving students’ self-confidence in speaking. And the students’ self-confidence affects to the students’ speaking achievement.